Approaching the limits of cationic and anionic electrochemical activity with the Li-rich layered rocksalt Li3IrO4. Issue 12 (December 2017) - Perez, Arnaud; Jacquet, Quentin; Batuk, Dmitry; Iadecola, Antonella; Saubanère, Matthieu; Rousse, Gwenaëlle; Larcher, Dominique; Vezin, Hervé; Doublet, Marie-Liesse; Tarascon, Jean-Marie
Abstract The Li-rich rocksalt oxides Li2 MO3 (M = 3d /4d /5d transition metal) are promising positive-electrode materials for Li-ion batteries, displaying capacities exceeding 300 mAh g–1 thanks to the participation of the oxygen non-bonding O(2p ) orbitals in the redox process. Understanding the oxygen redox limitations and the role of the O/M ratio is therefore crucial for the rational design of materials with improved electrochemical performances. Here we push oxygen redox to its limits with the discovery of a Li3 IrO4 compound (O/M = 4) that can reversibly take up and release 3.5 electrons per Ir and possesses the highest capacity ever reported for any positive insertion electrode. By quantitatively monitoring the oxidation process, we demonstrate the material's instability against O2 release on removal of all Li. Our results show that the O/M parameter delineates the boundary between the material's maximum capacity and its stability, hence providing valuable insights for further development of high-capacity materials. Anionic redox provides extra capacity for battery electrodes, but it is challenging to realize its full potential. Tarascon and colleagues report a record-high reversible capacity of 3.5 electrons per Ir in a Li3 IrO4 phase, and discuss the importance of increasing the ratio of oxygen versus transition metal.